GENDER DALAM TAFSIR JAWA: (STUDI ATAS TAFSIR AL-HUDĀ KARYA BAKRI SYAHID) - Suci Wulandari (QOF, 2018)
This article examined the interpretation of several verses in Tafsir al-Huda by Bakri Syahid, major in relation to gender issues. There are several themes studied, such as: the rewards of deeds of charity, the origin of the creation of man, polygamy, inheritance formula 1: 2, and leadership in the household. In this study, the author tried to understand the interpretation of Bakri with the interpretive-hermeneutical approach. This approach aims to describe and analyze the interpretation of the figures against the verses of the Qur’ān discussed in the theme of gender construction. The Qur’an interpretation that has been done by ulama can not be separated from the conditions of social culture surround them. It’s called prior text. Tafsir al-Hudā, the interpretation of Bakri’s work is one of them. His interpretation is influenced by Javanese culture, beside his military and his work as academics. It seems when he interpreted verses about woman in the Qur’an, Bakri accommodated the culture for woman and man in Java. In addition, the writer analyzed the existence of gender bias or not in their interpretation by using gender equality theory Mansour Fakih. This theory suggests that gender racism and gender differences manifest in five ways: a) subordination, b) marginalization, c) stereotypes, d) violence, and e) double burden. In the first three interpretations (the rewards of deeds of deeds, the origins of human creation, and polygamy), Bakri seems to carry equality. While two other things (in terms of inheritance formula 1: 2 and household leadership), the interpretation appears to contain subordination and marginalization of women.